A novel lncRNA LOLA1 may predict malignant progression and promote migration, invasion, and EMT of oral leukoplakia via the AKT/GSK‐3β pathway. Issue 10 (10th May 2021) - Liu, Wei; Yao, Yilin; Shi, Linjun; Tang, Guoyao; Wu, Lan
Abstract: Although dysregulation and dysfunction of long noncoding RNAs (lncRNAs) have been implicated in malignant behavior of oral squamous cell carcinoma (OSCC), whether aberrant lncRNAs play a role in the carcinogenesis of oral leukoplakia (OL) as the best‐known precursor of OSCC remains undetermined. Differentially expressed lncRNAs in the occurrence and progression of OL were studied by microarray and quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR). We found a novel key lncRNA n386251 that we named LOLA1 (lncRNA oral leukoplakia progressed associated 1) in the OL progression. The results of qRT‐PCR revealed that LOLA1 aberrant expression was validated in tissue samples and cell lines from the normal oral mucosa, OL to OSCC. Fluorescent in situ hybridization showed that LOLA1 expression localized predominately at the cytoplasm of Leuk1 cells. Cell function assays showed that LOLA1 significantly influenced cell migration, invasion, and epithelial–mesenchymal transition (EMT) protein expression. Potential mechanism experiments revealed that AKT/GSK‐3β signaling was involved in the regulatory mechanism of LOLA1 in OL progression. Remarkably, Kaplan–Meier analysis revealed that LOLA1 overexpression could predict malignant events of OL progression to OSCC. In conclusion, the current study for the first time profiled and validated the key lncRNAs related to OL progression. Importantly, we demonstrated that a novel lncRNA LOLA1 upregulation was associated with OL malignant progression, suggesting LOLA1 may be a predictive biomarker. Moreover, LOLA1 may promote migration, invasion, and EMT process in OL malignant progression via AKT/GSK‐3β pathway. Abstract : The current study for the first time profiled and validated the key long noncoding RNAs (lncRNAs) related to oral leukoplakia (OL) progression. Importantly, we demonstrated that a novel lncRNA LOLA1 upregulation was associated with OL malignant progression, and it may promote migration, invasion, and epithelial–mesenchymal transition process in OL malignant progression via the AKT/GSK‐3β pathway.